2020
DOI: 10.3390/ijms21041204
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated Aspect of Mucopolysaccharidosis Pathogenesis: Global Changes in Cellular Processes Revealed by Transcriptomic Studies

Abstract: Mucopolysaccharidoses (MPS), a group of inherited metabolic disorders caused by deficiency in enzymes involved in degradation of glycosaminoglycans (GAGs), are examples (and models) of monogenic diseases. Accumulation of undegraded GAGs in lysosomes was supposed to be the major cause of MPS symptoms; however, their complexity and variability between particular types of the disease can be hardly explained by such a simple storage mechanism. Here we show that transcriptomic (RNA-seq) analysis of the material der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 39 publications
4
77
0
Order By: Relevance
“…PRJNA562649). The quality of the RNA‐seq data was confirmed previously and assessed to be reliable on the basis of RT‐qPCR analyses of selected genes [12–14]. Because of the severity of the disease, fibroblasts are most often used type of cells in genetic and genomic studies on MPS; in fact, availability of other biological material is technically and ethically poor, due to conditions of patients.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…PRJNA562649). The quality of the RNA‐seq data was confirmed previously and assessed to be reliable on the basis of RT‐qPCR analyses of selected genes [12–14]. Because of the severity of the disease, fibroblasts are most often used type of cells in genetic and genomic studies on MPS; in fact, availability of other biological material is technically and ethically poor, due to conditions of patients.…”
Section: Resultsmentioning
confidence: 72%
“…RNA isolation was conducted in four biological repeats for each cell line (i.e., four independent cultures from different passages). The procedure was performed exactly as described previously [12].…”
Section: Rna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies clearly indicated that secondary and tertiary changes (after the primary GAG storage) in cellular processes contribute significantly to the development of disorders and symptoms appearing in the course of MPS (Gaffke et al 2019;Fecarotta et al 2020). Significance of this aspect of MPS pathomechanism has been highlighted recently by discoveries of multiple changes in expression of genes coding for proteins involved in various cellular mechanisms in MPS (Brokowska et al 2020;Gaffke et al 2020;Pierzynowska et al 2020;Rintz et al 2020). Therefore, in this work, we have analyzed transcriptomic data, focusing on expression of genes coding for regulatory proteins responsible for the control of cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models and studies in humans demonstrated that impaired GAG degradation causes a deep alteration of cellular homeostasis involving pathways unrelated to the GAG metabolism [10,11,[13][14][15][16]. Indeed, defects in the lysosomal degradation of GAGs can be associated with dysfunctions in several biochemical and physiological processes such as the abnormal composition of membranes with an impact on vesicle fusion and trafficking, altered ganglioside and cholesterol metabolism, proteinase deregulation, impairment of autophagy and mitochondrial functions, and others [14][15][16][17][18][19][20]. Thus, a more detailed understanding of the pathogenetic events downstream of the altered GAG metabolism is still required.…”
Section: Introductionmentioning
confidence: 99%